Applying a novel framework for the estimation of the full cost of water in a degraded rural watershed - A. Alamanos (IWA Publishing, 2021)
Water Resources Management's modern concerns include solutions on water scarcity, water quality problems and the use of economic and decision-support tools. Especially, the agricultural sector in South Europe under the requirements of the Water Framework Directive 2000/60/EC(WFD) remains a challenge. Most scholars so far doubt and criticize the implementation of the full cost of irrigation water, review papers highlight the limited progress, and fewer cases provide guidance on how to address this case. The present study applies a novel methodological framework for the estimation of the full cost of irrigation water, based on hydro-economic concepts such as: water balance, profits from agriculture, water value, water quality, monetary, opportunity and environmental costs. Originally, the method has been applied only once in a rural watershed with surface and groundwater resources. Here, a degraded Greek watershed using only groundwater resources is the study area, and the results of the two cases are compared. The model was also examined under demand management strategies and recommendations to scrutinize the effects and the applicability of the proposed measures in hydrological and economic terms. The findings give useful insights on the future management of achieving economic objectives with environmental constraints and the harmonization of Greek agriculture to the WFD. Highlights A previously presented methodology for the estimation of the full cost of irrigation water is now applied in another case, proving its consistency and establishing previous findings.; Extension of the method and new suggestions.; Comparison of case studies shows the method is suitable for Greek basins and water pricing analysis is required before tariff policy.; Novel hydro-economic approach.; Handy tool for local agencies.;